2021
DOI: 10.1016/s0140-6736(21)01638-x
|View full text |Cite
|
Sign up to set email alerts
|

Redefining β-blocker response in heart failure patients with sinus rhythm and atrial fibrillation: a machine learning cluster analysis

Abstract: Background Mortality remains unacceptably high in patients with heart failure and reduced left ventricular ejection fraction (LVEF) despite advances in therapeutics. We hypothesised that a novel artificial intelligence approach could better assess multiple and higher-dimension interactions of comorbidities, and define clusters of β-blocker efficacy in patients with sinus rhythm and atrial fibrillation.Methods Neural network-based variational autoencoders and hierarchical clustering were applied to pooled indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 26 publications
0
61
0
Order By: Relevance
“…Others have shown that AF causes electrical remodeling with longer effective refractory periods and slower conduction, predominantly in the PVs, which begets AF [ 101 ]. Together, these studies explain why beta-blockers, which ameliorate autonomic influences, slow the heart rate, and flatten APD restitution [ 102 ], may prevent AF in some patients [ 103 ]. They may also motivate the role of class I agents, which slow atrial conduction [ 104 ].…”
Section: Af Pathophysiology Within the Heartmentioning
confidence: 99%
“…Others have shown that AF causes electrical remodeling with longer effective refractory periods and slower conduction, predominantly in the PVs, which begets AF [ 101 ]. Together, these studies explain why beta-blockers, which ameliorate autonomic influences, slow the heart rate, and flatten APD restitution [ 102 ], may prevent AF in some patients [ 103 ]. They may also motivate the role of class I agents, which slow atrial conduction [ 104 ].…”
Section: Af Pathophysiology Within the Heartmentioning
confidence: 99%
“…Karwath et al. 1 in The Lancet investigated the question of whether there are clusters of heart failure patients in both sinus rhythm and atrial fibrillation that exhibit differential benefit from beta blocker medications. Among patients who have heart failure with reduced ejection fraction (HFrEF), beta blockers are a cornerstone medical therapy supported by substantial prior literature.…”
Section: Main Textmentioning
confidence: 99%
“… Summary A recent study by Karwath et al. 1 in The Lancet applied machine learning-based cluster analysis to pooled data from nine double-blind, randomized controlled trials of beta blockers, identifying subgroups of efficacy in patients with sinus rhythm and atrial fibrillation. …”
mentioning
confidence: 99%
“…The results of a currently published neural network-based analysis of 15,659 patients with heart failure and a mean left ventricular ejection fraction of 27% reported that the use of beta-blocker medication in the majority of patients with atrial fibrillation does not reduce mortality when compared to patients with sinus rhythm, suggesting that, to date, catheter ablation remains the only mortality-reducing treatment in this very common group of patients (Fig. 1 ; [ 8 ]).
Fig.
…”
Section: Origins Of Pulmonary Vein Isolation and Impact On Current Tr...mentioning
confidence: 99%